Impact of resection and ablation for single hypovascular hepatocellular carcinoma ≤2 cm analysed with propensity score weighting. (25th January 2018) - Takayasu, Kenichi; Arii, Shigeki; Sakamoto, Michiie; Matsuyama, Yutaka; Kudo, Masatoshi; Kaneko, Shuichi; Nakashima, Osamu; Kadoya, Masumi; Izumi, Namiki; Takayama, Tadatoshi; Ku, Yonson; Kumada, Takashi; et al.
Abstract: Background and Aims: Small hypovascular hepatocellular carcinoma (HCC) ≤2 cm is biologically less aggressive than hypervascular one, however, the optimal treatment is still undetermined. The efficacy of surgical resection (SR), radiofrequency ablation (RFA) and percutaneous ethanol injection (PEI) was evaluated. Methods: The 853 (SR, 176; RFA, 491; PEI, 186) patients were enrolled who met Child‐Pugh A/B, single hypovascular HCC ≤2 cm pathologically proven, available tumour differentiation and absence of macrovascular invasion and extrahepatic metastasis. Overall and recurrence‐free survivals were compared in original and a propensity score weighted pseudo‐population with 732 patients. Results: The median follow‐up time and tumour size were 2.8 years and 1.47 cm respectively. In original population, multivariate Cox regression showed no significant difference for overall survival among three groups. In pseudo‐population, Cox regression also revealed no significant difference for overall survival among them, although SR (HR, 0.56; 95% CI, 0.36‐0.86) and RFA (HR, 0.75; 95% CI, 0.57‐1.00) groups had significantly lower recurrence than PEI group. The overall survival rates at 3 and 5 years for the SR, RFA and PEI groups were 94%/70%, 90%/75% and 94%/73% respectively. Corresponding recurrence‐free survival rates were 64%/54%, 59%/41% 48%/33% respectively. Subgroup analysis revealed no significant survival benefit of SR compared with non‐SR. No treatment‐related death occurred. Conclusions: For patients with single hypovascular HCC ≤2 cm, no significant difference for overall survival was first identified among 3 treatment groups. The SR or RFA could be recommended, and PEI would be alternative to RFA. Abstract : See Editorial on Page415